The Capital Markets of Emerging Europe : Institutions, Instruments and Investors - Ong, Li.; Iorgova, Silvia (Washington, D.C. : International Monetary Fund, 2008)
Emerging European countries have made large strides in developing their local capital markets since the early-1990s. However, the rate of development has been widely disparate across countries and market segments, underpinned by the varying degrees of progress made in key areas such as establishing pricing benchmarks, adopting, implementing and enforcing securities laws and regulations, encouraging the growth of an institutional investor base, and providing adequate trading infrastructure. This paper provides an overview of the trends in the region's local capital markets, and examines the main factors that have contributed to their growth and effectiveness to date. It also discusses selected policy responses necessary to further improve the breadth and depth of these markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet